2016
DOI: 10.1186/s12889-016-3127-5
|View full text |Cite
|
Sign up to set email alerts
|

Global healthcare use by immigrants in Spain according to morbidity burden, area of origin, and length of stay

Abstract: BackgroundThe healthcare of immigrants is an important aspect of equity of care provision. Understanding how immigrants use the healthcare services based on their needs is crucial to establish effective health policy.MethodsThis retrospective, observational study included the total population of Aragon, Spain (1,251,540 individuals, of whom 11.9 % were immigrants). Patient-level data on the use of primary, specialised, hospital, and emergency care as well as prescription drug use in 2011 were extracted from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 41 publications
2
28
0
4
Order By: Relevance
“…On the other hand, although immigrants tend to be healthier when they arrive at a new country, which is known as the healthy immigrant effect, their health worsens with time in the new country quicker than the host population [ 41 , 42 ]. Previous studies show therefore a general increase in the use of health services after some years in the new country [ 16 , 43 ]. In our study, however, the pattern seems to be reversed for immigrants from Somalia and Gambia.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, although immigrants tend to be healthier when they arrive at a new country, which is known as the healthy immigrant effect, their health worsens with time in the new country quicker than the host population [ 41 , 42 ]. Previous studies show therefore a general increase in the use of health services after some years in the new country [ 16 , 43 ]. In our study, however, the pattern seems to be reversed for immigrants from Somalia and Gambia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the 1990s have shown that immigrants can only be provided with adequate health care if their specific needs and histories are born in mind. This is often neglected in emergency centres [ 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The average cost per visit in Global Clinic was lower than for physician`s general practice encounter in Finland in 2016 [9]. According to estimates [4] and evidence from actual service use [14] and actual costs [15], extending migrants` healthcare entitlements beyond emergency care is likely to cost less than estimated based on healthcare costs in the general population.…”
Section: Discussionmentioning
confidence: 99%